Tocotrienols may reverse the deleterious effects of nicotine-induced oxidative stress on embryo development in mice / Mohd. Hamim Rajikin … [et al.] - Rajikin, Mohd. Hamim; Chatterjee, Amar; Mohamed Nor Khan, Nor-Ashikin; Abdul Satar, Nuraliza (Research Management Institute (RMI), 2013)
The adverse effects of smoking on reproduction are well documented, yet the current trend of tobacco smoking among women still remains. Approximately 4% of Malaysian population aged ≥15 years are female smokers (WHO Policy, Strategy Advisory Committee for Tobacco Free Initiative Estimated, 2000). In general, people smoke cigarettes for the psychoactive effects of nicotine where it is believed that nicotine may enhance the sense of well-being, produce arousal or relaxation, help maintain vigilance, or reduce anxiety (Benowitz, 1988). However, nicotine has shown many potential adverse health consequences in reproductive or perinatal disorders including low birth weight, prematurity and spontaneous abortion (Benowitz, 1988), delay in conception (Zenzes, 1995) and the onset of menopause in female smokers (Midgette and Baron, 1990). Therefore, certain components in cigarette smoke may directly or indirectly interfere with embryo development and viability. Nicotine is present in cigarettes in amounts varying from 0.8 to 1.8 mg per cigarette depending on the brand and size of cigarette (Benowitz et al., 1983; Rosa et al., 1992). As much as 1.0 mg of nicotine is recorded to be absorbed by smoking a single cigarette (Barbieri et al., 1986). Nicotine is a toxic alkaloid and is quickly absorbed through the respiratory track, mucosa of the mouth and skin (Gandini et al., 1997). It has also been reported that lung appears to serve up as a reservoir for nicotine, which slows its entry into the arterial circulation, implying that even though almost all of the nicotine inhaled in each puff being absorbed in a few seconds, it may require 30–60 seconds or longer for the nicotine to be fascinated (Brewer et al., 2004).